6/9 is equal to 2/3 is equal to 4/6. Equivalent fraction visually. Equivalent fractions on the number line. Equivalent fractions on the number line.
Answer:1.56
Step-by-step explanation:
For constant of proportionality of k,
y=(1/k)*x
If y =9,
9=7/k
K=7/9=0.78
y=0.78x
y=0.78*2=1.56
When x
We are given the functions:
<span>P (d) = 0.75 d --->
1</span>
<span>C (P) = 1.14 P --->
2</span>
The problem asks us to find for the final price after
discount and taxes applied; therefore we have to find the composite function of
the two given functions 1 and 2. To solve for composite function of the final
price of the dishwasher with the discount and taxes applied, all we have to do
is to plug in the value of P (d) with variable d into the equation of C (P).
That is:
C (P) = 1.14 (0.75 d)
C (P) = 0.855 d
or
<span>C [P (d)] = 0.855 d</span>
Answer: 0.206
Step-by-step explanation: the probability of employees that needs corrective shoes are =8%= 8/100 = 0.08
Probability of employees that needs major dental work = 15% = 15/100 = 0.15
Probability of employees that needs both corrective shoes and dental work = 3% = 3/100 = 0.03
The probability that an employee will need either corrective shoes or major dental work = (Probability an employee will need correct shoes and not need dental work) or (probability that an employee will need dental work or not corrective shoes)
Probability of employee not needing corrective shoes = 1 - 0.08 = 0.92
Probability of employee not needing dental work = 1 - 0.15 = 0.85
The probability that an employee will need either corrective shoes or major dental work = (0.08×0.85) + (0.15×0.92) = 0.068 + 0.138 = 0.206 = 20.6%
The probability that an employee will need either corrective shoes or dental work = 0.206.
Please note that the word "either" implies that we must choose one of the two options (corrective shoes or dental work) and not both.
Hello from MrBillDoesMath!
Answer: (4b-6) log(a) = log (3c + d)
Discussion:
Take the log of both sides of the equation:
log ( a ^(4b-6)) = log (3c + d)
As the log functions causes exponents to become multiplexers, this equation is the same as
(4b-6) log(a) = log (3c + d)
Thank you,
MrB